Efficiency wages, unemployment and welfare: A trade theorists' guide - Max Albert; Jürgen Meckl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
The paper incorporates the efficiency-wage theory into an otherwise standard trade model. The model accounts for sector-specific job rents and involuntary unemployment while preserving decisive properties of the competitive fullemployment approach. The key results from the literature can be derived from special cases; e.g., raising minimum wages can reduce unemployment. Additionally, we derive new, counterintuitive results: (a) Emigration can raise home employment, (b) Immigrants might not only find employment but also raise employment for non-immigrants, (c) Investment can reduce employment, (d) Raising unemployment benefits can reduce unemployment.
Keywords: 330; Effizienzlohn; Außenwirtschaftstheorie; Arbeitsmarkttheorie; Theorie